2013
DOI: 10.1007/s00482-013-1370-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the German new back school

Abstract: On the basis of the sample studied, the new back school proved to be an effective treatment for short and long-term reduction of pain-related stress and associated psychological aspects. Maladaptive, passive coping strategies and higher depression scores were associated with a higher probability of success in terms of pain reduction and functional improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Accordingly, it is impossible to assess the conformity of physiotherapeutic treatment with the existing guideline recommendations. An earlier study with participants of the New German Back School [ 27 ] revealed a similar pattern of predominantly passive treatments in the history of the patients. In this study, participants with relatively low pain-related burden were surveyed in a secondary preventive setting.…”
Section: Discussionmentioning
confidence: 71%
“…Accordingly, it is impossible to assess the conformity of physiotherapeutic treatment with the existing guideline recommendations. An earlier study with participants of the New German Back School [ 27 ] revealed a similar pattern of predominantly passive treatments in the history of the patients. In this study, participants with relatively low pain-related burden were surveyed in a secondary preventive setting.…”
Section: Discussionmentioning
confidence: 71%
“…to enhance psychological outcomes in depression 30 , in women with menstrual disorders 31 , in reducing anxiety 32 , in glycemic control 33 , during cancer treatment 34 and, of course, in nCLBP 17 , is widely documented. Back school has proved useful in back pain management 35 but recently Borys et al 36 have proved that this program could be also useful to ameliorate painrelated stress and associated psychological aspects. Literature also describe the so-called fear-avoidance © C I C E d i z i o n i I n t e r n a z i o n a l i model, according to which people develop chronic musculoskeletal pain as a result of avoidant behavior based on fear 11,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Especially overly socially avoidant interpersonal behaviour can be treated successfully by interpersonal-based group therapy [ 35 ]. Wittingham [ 22 ] for example, developed a brief, semi-structured process group approach targeting reduction in interpersonal distress (Focused Brief Group Therapy, FBGT). Focus lies on specific interpersonal behaviours that will decrease the patient’s level of interpersonal distress.…”
Section: Discussionmentioning
confidence: 99%
“…The New German Back School integrates components of the classical Back School (exercise) and education based on psychological and social aspects. The back pain group participated in the Back School, with 12 one-and-a-half-hour theoretical and practical trainings held once a week [ 22 ].…”
Section: Methodsmentioning
confidence: 99%